A-70 Differences in Cognition and Disease Characteristics in Adult Vs. Late Onset Multiple Sclerosis. (30th August 2021) - Butler Pagnotti, Rachel M; Hua, Le Hanh; Miller, Justin B
Abstract: Objective: Cognitive impairment is a common sequelae of multiple sclerosis(MS), however, relatively little is known about cognitive impairment in late-onset MS (LOMS; symptom onset >50 years old). The present study investigated differences in disease characteristics and cognition in LOMS and adult-onset MS (AOMS). Methods: Archival medical records and neuropsychological evaluations from an MS specialty center were reviewed. Differences in disease characteristics between 57 LOMS and 124 AOMS patients were compared using chi-square or ANOVA. To investigate differences in cognitive functioning, age-adjusted standardized scores were compared via ANCOVA, using cardiac risk factors and disease duration as covariates. Results: Compared to AOMS (age range: 21–88; mean age: 49.66 +/−12.83), LOMS patients (age range 42–82; mean age: 61.88 +/− 8.57) had significantly more cardiac comorbidities (mean: 1.12+/−1.1 vs. 0.6+/−0.9; p < 0.01), shorter disease duration (mean years: 13.14+/−7.9 vs. 21.0+/−12.6; p < 0.001), and shorter time to diagnosis (mean years: 3.0+/−4.2 vs 6.5+/−8.5; p < 0.01). LOMS patients had similar Expanded Disability Status Scale scores and number of prescribed disease-modifying therapy as AOMS. LOMS patients demonstrated greater impairment on Brief Visuospatial Memory Test-Revised learning (F(1, 169) = 8.03, p < 0.05; d = 0.36) and delayed recall (F(1, 169) = 4.44, p < 0.05; d = 0.27), and on Wechsler Adult Intelligence Scale-4th edition Digit Span Backward (F(1, 176) = 5.68, p < 0.05; d = 0.41) and Sequencing (F(1, 176) = 11.90, p < 0.001; d = 0.55) subtests. Conclusion: Despite a shorter disease duration and quicker diagnosis, LOMS patients demonstrate similar levels of physical impairment. Moreover, even after accounting for differences in disease duration and cardiac risk, LOMS showed a greater burden of cognitive impairment than AOMS, which taken together, suggests an elevated rate of disease progression in LOMS.